(untitled) (gjstudies, 2021)
This study investigates the relationship between corporate sustainability reporting(CSR) and financial performance by employing a novel, cross-disciplinary methodology that integrates principles from ecological network analysis and information theory. Departing from conventional regression-based approaches that treat sustainabilitymetrics as independent variables, we conceptualize a firm’s sustainability report as acomplex information system. We introduce the Sustainability Information Coherence(SIC) index, a measure derived from the mutual information between environmental,social, and governance (ESG) disclosure categories and the structural entropy of thereport’s narrative and quantitative data linkages. Our core hypothesis posits that theinternal coherence and informational richness of sustainability reporting, rather thanmerely the volume or binary presence of disclosure, is a significant predictor of financial outcomes. We analyze a hand-collected dataset of 450 sustainability reportsfrom global firms across three sectors (Energy, Manufacturing, Finance) from 1998 to2004. Financial performance is measured via a composite index incorporating Tobin’sq, return on assets (ROA), and stock price volatility. Results from our constructedNetwork Influence Model (NIM) reveal a strong, non-linear association between highSIC scores and superior financial performance, particularly in environmentally sensitiveindustries. The relationship is moderated by the firm’s existing informational transparency, as measured by analyst coverage. We find that for firms with low baselinetransparency, improvements in SIC have a markedly stronger positive financial impact.This research contributes an original theoretical lens, viewing sustainability reportingnot as a cost or compliance exercise but as a strategic signal of managerial competenceand systemic risk understanding. Our findings suggest that regulators and investorsshould prioritize the quality and interconnectedness of sustainability information overits mere existence.